Lawfare as a Policy Tool in Sino-American Relations: The Case of Huawei CFO Meng Wanzhou - Zachary S Souders (Hatfield Graduate Journal of Public Affairs)
Competition between the United States and China is at an all-time high. Despite decades of diplomacy between the East and West, recent trends suggest the two powers are drifting further apart. To understand US-China relations, it is critical to understand major developments as they occur. This paper examines the geopolitical significance of United States v. Meng (2020), an extradition case in which US authorities requested the transfer of Chinese tech executive Meng Wanzhou to American jurisdiction. Despite US policymakers declaring Meng and Huawei to be threats to national security, the eventual dismissal of all charges Meng faced presents a puzzle to policymakers and academics alike, who wonder why such a high-profile case could be dropped years later. Through analyzing primary sources from the United States, China, and Canada, I conclude that the trial in question stems from larger geopolitical themes of US-China competition and represents an example of lawfare being used as US foreign policy tool. This trial has wide-reaching implications for the foreign policy strategies of the United States and China, notably in the economic, technology, and security arenas, and represents a rift from the international laws and norms surrounding sanctions, which have typically been a multilateral affair.